BREAKING THROUGH LANGUAGE BARRIERS: THE IMPORTANCE OF FOREIGN LANGUAGE LEARNING IN AN ERA OF GLOBALISATION - Husna Imro'athush Sholihah; Imelda; Hafidhun Annas (CV. ADIBA AISHA AMIRA, 2024)
The modern era of globalisation has fostered the importance of foreign language learning, where the need to communicate across cultures and participate in the global job market is increasing. This research uses the literature review method. The results show that globalisation has connected countries around the world, making it imperative for individuals to master more than one language to maintain competitiveness and relevance in the global market. In addition to economic benefits, learning a foreign language also contributes to personal development, such as improved memory, problem-solving ability, and individual creativity. However, learning a foreign language also presents various obstacles, such as time constraints, difficulty understanding new phonetics and grammar, and cultural barriers. The lack of exposure and practice with native speakers can compound the process of achieving fluency. To overcome these challenges, strong support, access to effective learning resources, and utilisation of modern technology and innovative methods are inevitable. Technology provides interactive platforms and educational resources that ease the learning process, making it more flexible and affordable